Assessment of Environmental Risks of Heavy Metals and their Role in Promoting Phytoplankton Growth in Tap Water - Yousif, Malath I. (American Journal of Biology and Natural Sciences, 2026)
Background: Drinking water is crucial that it is a second most needed substance for human life. About half of the world's population suffers from the problem of contaminated drinking water. Objectives: The current investigation presented a thorough assessment of heavy metal levels: lead, copper, cadmium, chromium along with phytoplankton frequencies at three stations. The results of statistical analysis revealed a significant (P=0.0011) decreased in Lead levels (15 ± 3) in 3rd Station as compared with (20 ± 5) in 1ST Station and (27 ± 2.645) in 2nd Station. Notably in all stations these levels seems to have a seasonal variation, where they reduced in summer season. Also, significant (P=0.0220) difference were recorded in Chrome levels, where their levels showed significant decrease in 1ST Station (51.666 ± 2.887) versus (64 ± 3.605) in 2nd Station and (60 ± 5) in 3rd Station; as well the Chrome levels were diminished in in summer season. On the other hand, Cadmium and Copper showed non-significant (P=0.3001, 0.6561 respectively) differences in the distribution of their levels across the studied stations and seasons. Chlorophyta showed the highest percent of appearance at 50.3%, while the least appeared phyla was Dinophyta at 5.36%, Cyanophyta and Bacillariophyta showed moderate percentage at (24.2% and 20.1% respectively). In addition, Cyanophyta and Chlorophyta were significantly (P=0.0006, 0.0284, respectively) more abundant at 3rd Station, with percentages of 50% and 46.7%, respectively. Dinophyta was significantly (P=0.0001) abundant in 2nd Station, accounting for 62.5%, while it did not appear at all in 1ST Station. Bacillariophyta was also significantly (P=0.0483) more abundant in 2nd Station, at 43.3%. Conclusion: Our study demonstrated spatial as well as seasonal differences in both chemical and biological indicators, emphasized the impacts of geographic position, anthropogenic activities, along with hydrological condition on quality of water.